Luqi Hana Steamboat / Luqmanul Hakim Jamingan ... [et al.] - Jamingan, Luqmanul Hakim; Mohd Nasri, Muhammad Haqimie; Khairul Nizam, Hanis Nabilah; Mohd Noh, Siti Nur Aina Khadijah (2022)
Luqi Hana Steamboat was started at 10 October 2022. We planned to name it as Luqi Hana Steambot because it is a combination of our name to always remind our starting point of hard work together as a partner and also as a strong bonds of friendship. This business main dish is a steamboat theme which involving variety of fresh seafoods, cooked meals, desserts and drinks. This business is a partnership business with 4 partners which is Luqmanul Hakim Bin Jamingan, Muhammad Haqimie Bin Mohd Nasri, Hanis Nabilah Binti Khairul Nizam, Siti Nur Aina Khadijah Bin Mohd Noh. We have different skills and that is what will benefits our business and will develop with varieties of ideas that come from each of us. In my opinion, different perspective in company is a critical part to grow the business successfully. So, each of us must go all out doing their work to achieve this company visions, missions and objectives. The Luqi Hana Steamboat have planned to use a proper operating planning and a lot of marketing strategies that will improve the quality of our business. This makes us become one, sharpen our creativity to think about ways to improve this business. We shared ideas and plans for the marketing strategies to make our business run smoothly and well-known throughout Malaysia. Some of the marketing strategy is by using social media platform. In this era of modernization, we can say that most of human being are a smart phone user. With the existence of a smart phone, everything is just a one click away. The power of internet are also unbelievable where everything can go viral and catch whole world attentions in just a few seconds. With media social such as Instagram, Facebook, Tiktok and others, Luqi Hana Steamboat can be promoted everyday and anytime. This platform also will be our main medium to deal and contact with our customers. For the market, we chose Kampung Jenderam Hulu Dengkil as our location because of its strategic characteristic. Luqi Hana Steamboat located near the UniKL Malaysian Institute of Aviation Technology which have gained regular customers for so many years. Therefore, we believe that with this advantages, we can make our business grow bigger, stronger and more success. For conclusion, we do take serious in many aspect such as the quality of the product we use, the service that we provide and the menu that we offered to our customers. We strongly hold onto “ a satisfied customer is the best business strategy of all “ quotes by Michael LeBoeuf